Attitudes and intentions to support biopharming. (21st November 2007) - Cook, Andrew J.; Fairweather, John R.
This study measures public intentions in New Zealand to support the biopharming of plants and animals. A model is developed of intentions to support biopharming in a referendum using attitudes, social pressure and self-identity as determinants of intention. Data were collected using a national postal survey (N = 565). Key findings were that self-identity, attitude and perceived social pressure were significant in determining intention and beliefs about biopharming were strongly linked to attitude. Changes in intention given the nature of its determinants are discussed. These changes hinge upon changes in positive and negative beliefs about biopharming that are shown to affect attitude and subsequently upon the intention to support biopharming.